The architecture of beliefs: teachers and learners' belief systems about L2 pronunciation teaching and learning in EFL classes in a brazilian context - Costa, Bruno Coriolano de Almeida (2022)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão, Programa de Pós-Graduação em Inglês: Estudos Linguísticos e Literários, Florianópolis, 2022.